Analysis of Community Participation in Village Development in Majalengka Regency - Putri Wulan Supriatin; Siti Khumayah (Journal of Comprehensive Science, 2026)
Community participation is a fundamental element in achieving sustainable village development because it enables communities to become active actors in planning, implementing, utilizing, and evaluating development programs. However, in many villages, community involvement remains largely procedural and has not yet reached an optimal level of collaborative participation. This study aimed to analyze community participation in village development in Ciparay Village, Leuwimunding District, Majalengka Regency, including the supporting factors and obstacles influencing participation. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, direct observations, and documentation involving key and supporting informants, including the village head, village secretary, and community representatives. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion verification. The results showed that community participation occurred throughout the development process, including decision-making, implementation, utilization of development outcomes, and evaluation. Community involvement was relatively strong in planning, infrastructure implementation, and the utilization of development programs. However, participation in the evaluation stage remained limited due to insufficient public understanding of regulations, limited dissemination of information, and time constraints. The study concluded that although community participation in Ciparay Village had been implemented effectively, strengthening community capacity, transparency, and voluntary involvement was necessary to achieve more sustainable and collaborative village development.